Decision-making factors of pharmacy customers purchasing over-the-counter complementary and alternative medicine for stress. Issue 3 (December 2017) - Clayton, Kevin; Luxford, Yoni; Stupans, Ieva
Abstract: Introduction: The use of complementary and alternative medicine (CAM) is increasing and some of this CAM is purchased as self-directed treatment for stress, a practice that may be very useful but dangerous if incorrectly applied. This paper reports on the findings of an Australian qualitative study involving semi-structured interviews to explore factors in the decision-making process of pharmacy customers purchasing over-the-counter CAM products for stress. Methods: Interview questions were based on the CAM Healthcare Model which takes into account a broad range of factors including values, beliefs and personal factors. Results: We report that thematic analysis of the data illustrated four core concepts: CAM was the participants' first choice, self-sought information was always checked, a willingness or desire to tell their doctor was evident and there was a level of dissatisfaction with conventional healthcare. These concepts align closely with the personal trait of self-care ability/tendency which, on closer examination, manifests in the key theme, the need for control. Conclusions: The findings illustrate important aspects of the decision-making process in purchasing CAM products for stress and point to areas of future research for pharmacists and pharmacy educators.